2019
DOI: 10.3390/ijerph16204036
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Production under Climatic Risks: Perception, Perceived Impacts and Adaptations in Punjab, Pakistan

Abstract: The changing climatic conditions coupled with fodder availability have posed severe challenges and threats for the dairy sector in Pakistan. The current paper determines the influence of climate change on the dairy sector in Pakistan. Comprehensive data set was collected from 450 farmers. The majority of farmers experienced the climate change and its variability and explained that severity and frequency of climatic extreme events such as droughts, heat waves, floods, pests and diseases and humidity is increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 71 publications
(108 reference statements)
2
17
0
1
Order By: Relevance
“…Few studies to date have analyzed the economic damage of flooding on livestock farms; those that have been carried out, especially in developing countries, consider the damage to livestock a consequence of flooding, but the studies do not give the damage a dimension (e.g., the increased incidence of a certain disease as a consequence of the poor hygiene conditions of a farm after flooding is reported but without any value associated with its variation) [18,19]. Other studies in developed countries quantify the economic impact of flooding on livestock, but they do so from a territorial scale, thus comparing different areas in the same region [20,21].…”
Section: Theoretical Background Flooding Damage To Livestock Production: a Case Study Of Dairy Cattle Herdsmentioning
confidence: 99%
“…Few studies to date have analyzed the economic damage of flooding on livestock farms; those that have been carried out, especially in developing countries, consider the damage to livestock a consequence of flooding, but the studies do not give the damage a dimension (e.g., the increased incidence of a certain disease as a consequence of the poor hygiene conditions of a farm after flooding is reported but without any value associated with its variation) [18,19]. Other studies in developed countries quantify the economic impact of flooding on livestock, but they do so from a territorial scale, thus comparing different areas in the same region [20,21].…”
Section: Theoretical Background Flooding Damage To Livestock Production: a Case Study Of Dairy Cattle Herdsmentioning
confidence: 99%
“…In contrast with previous studies, our quantitative study used a survey approach and employed multi-stage stratified random sampling to collect the primary data from a sample of 612 farmers, determined through Cochran's formula [37,[55][56][57]. A well-designed structured questionnaire was used to collect the data through interviews with the farmers.…”
Section: Data Collectionmentioning
confidence: 99%
“…They found that climate change and CO 2 emission had an adverse impact on agricultural productivity in the context of Pakistan. Increasing temperature severely affected crop production and also decreased livestock production, which has the major contribution (60%) in the agriculture sector [15]. Increases in temperature for a long time ultimately leads to drought and shortage of water availability that is essential for agricultural production and results in decreased agricultural production.…”
Section: Long-run Analysismentioning
confidence: 99%
“…Since the last two decades, the agriculture sector growth of Pakistan's economy has been severely devastated due to unpredicted climatic changes. Continuous increase in temperature, a series of floods from 2010 to 2014, long span of droughts, and occurrence of new pests and diseases has greatly affected the agricultural production [14,15]. It is worth noting that climatic changes declined the agricultural production and solemnly threatened the food security of the country.…”
Section: Introductionmentioning
confidence: 99%